Hair Growth Stimulation in Testosterone-Induced Alopecic Mice: A Comparative Study between Topical Clove Oil 10% Topical Minoxidil 5% - Abdul Ghany, Banan; Qasim, Huda I. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Hair follicle degradation characterizes androgenic alopecia (AGA). Deterioration shortens anagen and lengthens telogen, turning terminal hairs into vellus hairs. Males and females have this prevalent sickness. Antibacterial, anti-inflammatory, and antioxidant Syzygium aromaticum may treat it.Objectives: To investigate Syzygium aromaticum as a hair growth booster in testosterone-induced alopecia as an alternative to allopathic treatments with fewer side effects.Methods: A controlled experimental animal study at College of Pharmacy/ University of Baghdad was conducted from November 2022 to December 2024. Male BALB/c mice weighing 25–30 grams and aged 8–12 weeks were used. Alopecia treatment often uses 5% minoxidil (0.1 mL). Alopecia was treated with 10% Syzygium aromaticum oil (0.8 mL). A 5% testosterone solution (100 µL) caused baldness in mice. Four groups of eight animals were randomly assigned: No treatment was given to Group I (Negative Control) after dorsal hair shaving. Group II (Alopecia Control) received only 5% testosterone. Group III (Minoxidil Group) received 5% testosterone and 5% minoxidil. Group IV (Clove Oil Group) received 5% testosterone and 10% Syzygium aromaticum oil.Results:  In Group II, testosterone-induced alopecia caused significant decreases in Anagen/Telogen A/T ratio (1.12 ± 0.09) and follicular density (4.8 ± 0.5 follicles/field) compared to the control group (Group I: 3.91 ± 0.24; 10.2 ± 0.7 Compared to the induced group, 5% minoxidil treatment (Group III) significantly increased A/T ratio (3.56 ± 0.20) and follicular density (9.5 ± 0.6). Group IV clove oil treatment showed significant A/T ratio improvement (3.32 ± 0.18), but comparable follicular density (8.8 ± 0.9) to minoxidil was insignificant.Histology corroborated these findings, showing that minoxidil and clove oil groups had higher follicle counts and better follicular architecture, with the former having more clustered and the latter more horizontal.Conclusion: Androgenic alopecia treatments may be replaced by Syzygium aromaticum. It needs human trials to prove its efficacy and safety.